Pendampingan Pembuatan Business Plan Repositioning Hotel Warna Kedaton Post COVID-19 - I Gusti Agung Gede Witarsana; Ni Putu Diah Prabawati (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2021)
Hotel Warna Kedaton is located in the city of Denpasar, precisely on Jalan Jayagiri Utara number 1 Bali. This hotel has Balinese architecture with basic facilities in the form of 49 guest rooms, supporting facilities such as restaurants, swimming pools and meeting rooms. However, the tight business competition makes this hotel must innovate to be able to compete with its competitors. In addition, the current COVID-19 pandemic has also had an impact on the sustainability of the hotel business. The purpose of this activity is to provide proposals for repositioning as an effort to reach more consumers, compete with competitors, and of course to revive the color of this hotel. This activity is aimed at the owner, employees of the Warna Kedaton Hotel and students of the 2020 Hospitality Administration Study Program C with a total number of 8 participants. This activity is carried out using the mentoring method in the form of lectures, discussions and direct practice. The results of this activity are in the form of making a business plan that emphasizes the proposed repositioning by making changes to the hotel concept, design, marketing, service, as well as hotel organization and management to become a boutique hotel.